Myelography with lopamidol. - Lamb, J T; Holland, I M (American Journal of Neuroradiology, 1983)
Two hundred patients who underwent myelography with iopamidol were independently assessed as to film quality and adverse side effects. Comparison was made with a similarly assessed group of 1,000 patients who underwent myelography with metrizamide. Diagnostic quality was generally excellent with both contrast media. The incidence of side effects, notably vomiting and headache, was significantly less with iopamidol but remains appreciable. More severe side effects may occasionally occur with either contrast medium.